Peran Pendamping Pelayanan Sosial pada Anak dalam Program Rumah Pintar di Yayasan Fajar Sejahtera Indonesia (YAFSI) Kota Medan - Nurul Fadillah Nasution; Erni Asneli Asbi (Yayasan Literasi Sains Indonesia, 2023)
The role of companion is needed to create children who have character and skills. Companions help, direct, support and provide solutions for children to develop further and become children with character. This research aims to find out the role of social service companion for children in the Program Rumah Pintar at YAFSI and what are the obstacles in the YAFSI Program Rumah Pintar. The method used in this research is a qualitative method with a descriptive approach to analyze/describe the role of companions in the Program Rumah Pintar. The data collection techniques used were interviews and observation. The results of this research show that the role of the companion is a facilitator, provider of reinforcement, provider of protection and support for children in the Program Rumah Pintar so that children with character are created, in the process obstacles were found in the Program Rumah Pintar, namely funding constraints, time constraints, and human resource (HR) constraints.